Assessing Speech Perception in Children With Hearing Loss: What Conventional Clinical Tools May Miss. Issue 2 (March 2015) - Hillock-Dunn, Andrea; Taylor, Crystal; Buss, Emily; Leibold, Lori J.
Abstract : Objectives: This study tested the hypothesis that word recognition in a complex, two-talker masker is more closely related to real-world speech perception for children with hearing loss than testing performed in quiet or steady-state noise. Design: Sixteen school-age hearing aid users were tested on aided word recognition in noise or two-talker speech. Unaided estimates of speech perception in quiet were retrospectively obtained from the clinical record. Ten parents completed a questionnaire regarding their children's ease of communication and understanding in background noise. Results: Unaided performance in quiet was correlated with aided performance in competing noise, but not in two-talker speech. Only results in the two-talker masker were correlated with parental reports of their children's functional hearing abilities. Conclusions: Speech perception testing in a complex background such as two-talker speech may provide a more accurate predictor of the communication challenges of children with hearing loss than testing in steady noise or quiet. Abstract : School-age hearing aid users were evaluated on aided word recognition in speech-shaped noise or two-talker speech. Unaided estimates of speech perception in quiet (SRT and PBK scores) were retroactively obtained from the clinical record. Children's clinical PBK scores were related to performance on the lab test in noise, but not in two-talker speech. Performance in two-talker speech, but not performance in noise, was correlated to parent report of their children's functional receptive communication impairment on a survey tool. Results suggest that complex speech perception tasks such as the one used here may provide valuable insight into real-world receptive communication ability.